Representasi Konsep Kecantikan dalam Video Music SNSD Gee - Banurea, Rima Nusantriani (Jurnal Sosiologi Agama, 2017)
Beauty is never ending concept. It always redefined, renewed, and reconstructed by actor who have a power like media to socializing and spreading it into the world. Therefore media can changing and determining what is the right concept of beauty not only for now but also for future. Music Video is one of many forms of media which can spreading any ideas or concepts like beauty amazingly through both a song and the story. The successful of Music Video Gee makes Korean Girl Band, SNSD, famous and gets a lot attention from many countries, like Indonesia. This Music Video is very fresh and different from the other Music Videos of Korean Girl Band or Boy Band at that time. But, Music Video Gee is not neutral. In that video, there is hidden concept of beauty which trying to represented by SNSD. This article will analyzing what is the code of beauty like and how is the beauty represented in that video. Keyword: Beauty, Music, Representation.